Unveiling The Unseen Struggle: Impostor Phenomenon in Intermediate Level Students - Cabacungan, Mary Angelie Sagun; Dela Cruz, Rhea Famucol; Orgas, Azilei Del Rosario; Parong, Hannah Naomi Nuñez; Ramos, Jansel Matining; Soro, Nicole Angela Serrano (Jurnal Psikologi Perseptual, 2025)
The aim of this study is to investigate impostor phenomenon among intermediate-level students, analyzing their unseen struggles within their academic performance. The mixed method, particularly the explanatory sequential design, was utilized to gather data from the intermediate-level students of Cabanatuan East Central School. Through the comprehensive analysis of gathered data from survey questionnaires to semi-structured interviews, the study reveals that intermediate-grade level students exhibit a moderate level of impostor phenomenon, indicating occasional feelings of inadequacy and self-doubt. The researchers also discovered the emergence of five themes summarized as FLARE, which highlights various aspects of the participants’ experiences in navigating academic challenges. However, the study also highlighted the intricate interplay of personal satisfaction, aspirations, and social dynamics in academic and personal development. Moreover, the study findings suggest that factor birth order factor shows a notable relationship. The researchers came up with the idea of creating the Flare-Up program as an intervention to empower students by helping them recognize impostor phenomenon, fostering a positive self-image, equipping them with coping tools, promoting a growth mindset, and creating a supportive environment. Recommendations were also provided to create a strong parental support system that may help children set realistic expectations for themselves.